PEMBERDAYAAN PENYULUH MUDA HAMA DAN PENYAKIT DI LABORATORIUM PENGAMATAN DAN PERAMALAN HAMA DAN PENYAKIT TANAMAN DAN PERKEBUNAN WILAYAH SURAKARTA DI PALUR SUKOHARJO MELALUI PENDAMPINGAN DAN APLIKASI AGEN PENGENDALI HAYATI PGPR - Pramono Hadi; Rismawati; Dwi Sulilarto; Tria Rosana Dewi; Irma Wardani; Siti Nurlela (Bajang Institute, 2021)
The ability of young counsellors is extraordinary in adoption and technology. Obstacles are directed there is no special program to young extensionists for training and mentoring in the utilization of natural materials for optimization of the use of PGPR. This service technique is to conduct empowerment and mentoring that is structured and massive to ensure the success of mentoring young extensionists. Community service in the form of empowerment and mentoring of young extensionists in collaboration with the Pest and Disease Observation Center in Sukoharjo, shows that in the manufacture of PGPR biological control agents, making biological control agents secondary metabolites of Trichoderma sp. and Beauveria bassiana, inoculation of Trichoderma sp., Beauveria bassiana spores and Paenibacillus polymyxa bacteria, and the manufacture of ECG (Sugar Potato Extract), can make PGPR biological control agents from bran, terrazzo and lime water. The results of young extension services are as follows: 1) The empowerment of young extensionists has been able to create a biological control agent of secondary metabolites of Trichoderma sp. and Beauveria bassiana. Have been able to make it with good and correct stages; 2) Empowerment of young extensionists can already Inoculate spores Trichoderma sp., Beauveria bassiana and bacteria Paenibacillus polymyxa. Have been able to make it with good and correct stages; 3) Empowerment of young extensionists already Making ECG (Sugar Potato Extract). Have been able to make it with good and correct stages. Empowerment is going well, and it is necessary for continuous mentoring to ensure that young extensionists continue to update information on the development of special technology utilization of PGPR.